SISTEM e-FILLING DAN KEPATUHAN WAJIB PAJAK DI WILAYAH KPP PRATAMA BOJONEGORO - Suprapto .; Ananda Ulfa Karunia (Sekolah Tinggi Ilmu Ekonomi Cendekia Bojonegoro, 2019)
This quantitative study aims to determine the effect of the application of the eFilling system to Taxpayer Compliance in the area of the Bojonegoro Tax Office. The population is 5,543 people with a sample of 45 individual taxpayers who report their tax returns at the KPP Pratama Bojonegoro. Research data collection techniques using a questionnaire. The analysis test used includes the t test, the coefficient of determination (R²), and data analysis techniques with simple linear regression analysis, using the SPSS version 22 program. The results of the study show that the application of the e-Filling system has a positive and significant effect on tax compliance. This can be seen from the results of the partial hypothesis test (t test), namely the value of tcount 6.941 is greater than ttable 2.021 with a significance level (sig.) greater than alpha 0.000 <0.05 which means that Ho is rejected and Ha is accepted with the information that there is an influence positive and significant between the application of the e-Filling system and taxpayer compliance. Based on the conclusions obtained from the results of the analysis, the advice given is for taxpayers to use e-Filling to get a lot of convenience in reporting the annual tax return.